Novi nahajališči puhaste breze (Betula pubescens Ehrh.) in smrdljivega brina (Juniperus sabina L.) v Julijskih Alpah - Dakskobler, Igor (Gozdarski vestnik, 2010)
The article describes new localities and sites of two rare species in the dendroflora of the Julian Alps. Betula pubescens Ehrh. was found in the glacial cirque of Za Akom in the Martuljek chain, in the subalpine beech forest (Polysticho lonchitis-Fagetum) at the juncture with Alpine dwarf pine stands. It grows on rendzina, at the orographic timberline, conditioned by avalanches. The new locality of Juniperus sabina L., the first definite locality in the entire Julian Alps, is in some 100-m-high, sunny (southeast) wall under Mt. Hohkovbl (Mt. Matajurski vrh) in the ridge Peči (the Tolmin-Bohinj Mountains) above the village of Rut in the upper Bača Valley.
Keywords: dendrologija; Betula pubescens Ehrh.; breza; Slovenia; Slovenija; Juniperus sabina L.; dendroflora; gozdni rezervati; Julian Alps; Julijske Alpe